Examining the Influence of CEO Characteristics and Brand Image on Performance of Food and Beverages MSMEs in Indonesia: The Mediating Role of Competitive Advantage - Dewi, Irra Chrisyanti (International Journal of Business, Law, and Education, 2023)
Delve into the dynamic world of micro, small, and medium-sized enterprises (MSMEs) within Indonesia's vibrant food and beverages industry. This captivating study goes beyond the surface, exploring the intricate relationships that shape these businesses. We zero in on the captivating influence of CEO characteristics and the magnetic power of brand image. Unravel the mystery of how competitive advantage, like a skilled mediator, intertwines these factors, driving performance to new heights. Armed with data from a comprehensive survey of 210 respondents, our quantitative analysis paints a vivid picture. Brace yourself for the revelation: CEO Characteristics and Brand Image are not just players; they are the star performers, significantly impacting the dazzling world of Food and Beverages MSMEs. And there's more—Competitive Advantage takes center stage, weaving the threads of CEO Characteristics and Brand Image into a tapestry of success. As with any compelling narrative, this research isn't without its limitations. However, it sparks the flames of curiosity, paving the way for future explorations to unravel the deeper layers of this captivating story.